Decolonizing Ourselves: An Investigation into Decolonial Relational Ethics - Adamavi-Aho Ekué, Amélé (International review of mission, 2023)
This article outlines some key steps and motifs for developing a decolonial relational ethics that will be vital not just to the work of decolonization but also to the practice of the ecumenical movement if it is to both add its weight to the calls for decolonization and itself be decolonized. The author interrogates key dimensions of her own field of study in Christian ethics and engagement in the ecumenical movement. She highlights some of the key spaces and often marginalized communities and persons who can shape the ecumenical movement's further engagement in decolonization. It offers a critique and a vision rooted in the author's lived experience and the scholarship of decolonization while seeking application in methodologies for colonial systems, relationships and mindsets to be challenged and reset.